You want to sell this to me twice!? How perceptions of betrayal may undermine internal product upgrades - Janina Garbas; Sebastian Schubach; Martin Mende; Maura L. Scott; Jan H. Schumann (Journal of the Academy of Marketing Science, 2022)
Physical products (e.g., cars, smartphones) increasingly evolve into dynamic service platforms that allow for customization through fee-based activation of restricted add-on features throughout their lifecycle. The authors refer to this emerging phenomenon as "internal product upgrades". Drawing on normative expectations literature, this research examines pitfalls of internal product upgrades that marketers need to understand. Six experimental studies in two different contexts (consumer-electronics, automotive) reveal that consumers respond less favorably to internal (vs. external) product upgrades. The analyses show that customer-perceived betrayal, which results from increased feature ownership perceptions, drives the effects. Moreover, this research identifies three boundary conditions: it shows that the negative effects are attenuated when (1) the company (vs. consumer) executes the upgrading, and (2) consumers upgrade an intangible (vs. tangible) feature. Finally, consumers react less negatively when (3) the base product is less relevant to their self-identity.
Keywords: 330; Dynamic service platforms; Product modifications; Internal product upgrades; Consumer betrayal; Normative expectations; Psychological ownership